Electron transport properties of dssc based on ZnO nanowire arrays - Nuraje, N.; Ilyassov, B.R.; Abzhanova, D.B. (ҚарМУ баспасы, 2015)
ZnO nanorod arrays were synthesized by hydrothermal method for 8, 10, and 12 hours. The array synthesized for 10h had the highest surface area and aspect ratio, and DSSC based on the 10h nanorod array revealed the best photovoltaic performance. The electron transport properties of DSSC based on the ZnO nanowire arrays were investigated by Electrochemical Impedance Spectroscopy (EIS).
Keywords: ZnO nanowire arrays; electron transport properties